Author Functions in Lars Kepler's The Hypnotist: An Analysis - Merkley, Taylor (MacEwan University Student eJournal, 2020)
This paper examines Foucault's notion of the author function as it pertains to Lars Kepler's bestselling 2011 crime thriller, The Hypnotist. Lars Kepler is the pseudonym of a Swedish husband-wife writing duo, making him the perfect subject for analysis centering on illusory notion of the author. This paper will answer these questions: Who is the true author of The Hypnotist? What factors influence the author function of this bestelling novel? And what can The Hypnotist phenomenon tell us about the relationships between authors and their readers? This paper will demonstrate that no literary works may be ascribed to an individual person, and that authors hold no privileged knowledge of the works they produce, because authors cease to be authors the moment pen is lifted from page.